Home in the Poetry of Saudi Arabia Poets: Mohammad ibn 'Abboud Al-'Amoudi an Example of a Distinguished Arab (2) - Yahya Saleh Hasan Dahami (UIN Sunan Gunung Djati Bandung, 2023)
The poet communicates the graceful emotions that rise in the hearts of every person toward their homeland because of their love for it. Saudi poets enjoy writing poetry that celebrates the dignity of nationalism. The love of one's homeland, obsession with it, laboring for it, defending and preserving it, and having it run in one's soul are all aspects of nationalism. The researcher aspires to highlight Mohammad ibn 'Abboud Al-'Amoudi's expertise, knowledge, and competence while also highlighting his love for his homeland, the Kingdom of Saudi Arabia, through the poem